Self-perceived effects of lucid dreaming on mental and physical health - Erlacher, Daniel; Schredl, Michael; Stumbrys, Tadas (International journal of dream research, 2021)
Anecdotal evidence that lucid dreaming might contribute to mental and physical health has been widely reported in the literature. Empirical research, though, is scarce. A brief questionnaire eliciting self-perceived benefits of lucid dreaming on mental and physical health had been completed by 386 participants who had lucid dream experiences. About 90% of the participants reported some benefit of lucid dreams on their waking life including mental and physical health. This benefit was related to higher lucid dream frequency, trait mindfulness, and spirituality. These promising results should encourage researchers to develop a manualized lucid dream therapy and test its effect on physical and mental health in a randomized waiting-list pre-post design. Qualitative research can answer questions regarding the specific mechanisms, i.e., how does lucid dreaming contribute to well-being in waking life in the long run.
Gesehen am 18.01.2021